An ameliorated Round Robin algorithm in the cloud computing for task scheduling - Nermeen Ghazy; Afaf Abdelkader; Mervat S. Zaki; Kamal A. Eldahshan (Institute of Advanced Engineering and Science, 2023)
Cloud computing is an advanced technology that offers types of assistance on requests. Because of the huge measure of requests got from cloud clients, all requests should be managed efficiently. Therefore, the task scheduling is critical in cloud computing. The provision of computational resources in cloud is controlled by a cloud provider. It is necessary to design high-efficiency scheduling algorithms that are compatible with the corresponding computing paradigms. This paper introduces a new task scheduling method for cloud computing called an ameliorated Round Robin algorithm (ARRA). The proposed algorithm develops an optimal time quantum based on the average of task burst time using fixed and dynamic manners. The experimental results showed that the ARRA significantly outperformed other algorithms including improved RR, enhanced RR, dynamic time quantum approach (ARR) and enhanced RR (RAST ERR) in terms of the average waiting time, average turnaround time and response time.